New Techniques for Optimizing the Norm of Robust Controllers of Polytopic Uncertain Linear Systems - Buzachero, Luiz F. S.; Assuncao, Edvaldo; Teixeira, Marcelo C. M.; Silva, Emerson R. P. Da (IntechOpen, 2012)
None